The Chinese Image reflects in the Commoner Genre Character: Case Study of Geng Xingguang from the TV Series “Bright Star” - Wissanuwong, Lalida (Journal of International Studies, Prince of Songkla University, 2024)
This article aims to explore the portrayal of Chinese identity within the context of ordinary character archetypes (小人物) through the case study of Geng Xingguang (耿星光) from the TV drama series "Bright Star" (星光灿烂). By examining the character, it becomes evident that the reflection of Chinese identity is closely tied to the authentic cultural context of Chinese life, encompassing four essential aspects: 1) love and compassion for others, 2) morality and ethics, 3) gratitude, and 4) a positive influence on those around them. Geng Xingguang, the protagonist, serves as a prime example of the values that modern Chinese society should uphold, emphasizing the significance of empathy, understanding, and caring for others, as well as the preservation of these virtues and ethics rooted in traditional Chinese culture. The character highlights the notion that an individual's acceptance within society is not solely determined by their intelligence or ability but rather by their moral character. The concept of "goodness" serves as a moral standard that shines through in this character study.